Classical relativistic systems of charged particles in the front form of dynamics and the Liouville equation - Nazarenko, A.; Tretyak, V. (Condensed Matter Physics, 2000)
Classical relativistic system of point particles coupled with an electromagnetic ﬁeld is considered in the three-dimensional representation. The gauge
freedom connected with the chronometrical invariance of the four-dimensional description is reduced by use of the geometrical concept of the forms
of relativistic dynamics. The remainder gauge degrees of freedom of the
electromagnetic potential are analysed within the framework of Dirac's constrained Hamiltonian mechanics in the front form of dynamics. The results
are applied to the problems of relativistic statistical mechanics. Based on
the corresponding Liouville equation the classical partition function of the
system is written down in a gauge-invariant manner and an integration over
ﬁeld variables is performed. Розглянуто класичну релятивістичну систему точкових частинок у
взаємодії з електромагнітним полем у тривимірному зображенні. За
допомогою геометричної концепції форм релятивістичної динаміки
виключається калібрувальна свобода, пов’язана з хронометричною
інваріантністю чотиривимірного опису. Решта калібрувальних ступенів вільности електромагнітного потенціалу аналізується в рамках
гамільтонової механіки з в’язями Дірака у фронтовій формі динаміки.
Одержані результати застосовано до проблем релятивістичної статистичної механіки. На основі відповідного рівняння Ліувіля записано статистичну суму системи у калібрувально-інваріантний спосіб та
здійснено інтеґрування за польовими змінними.